ANALYSIS OF COLLECTION PRESERVATION IMPLEMENTATION IN SCHOOL LIBRARIES - Irmawati Irmawati; Nur Fadillah Rusli; Irvan Muliyadi; Saenal Abidin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
This study, entitled